IMPORTANCE-PERFORMANCE ANALYSIS OF INDONESIA UNIVERSITY OF EDUCATION (UPI) LIBRARY SERVICES TO OPTIMIZE ACADEMIC AND RESEARCH QUALITY IMPROVEMENT - Wahyudin, Uyu (EDUTECH, 2015)
Abstract. This study aims to analyze the quality of services provided by UPI library to UPI students and to find out and analyze the extent of students’ level of satisfaction on the services provided. It also aims to know the compatibility between the service performances and students’ expectation or interest as the users of library services. This study used mixed approach of qualitative and quantitative and importance-performance analysis in order to determine the students’ satisfaction index on library services. The data was analyzed using grade of Students Satisfaction Index (IKM) which was calculated using the weighted average value of each service element. Importance-Performance Analysis was used to see the level of compatibility between expectation and service quality. The results showed that the performance of UPI library services was in good category. The service element perceived to be the best was related to service security while the worst was staff discipline. Furthermore, there was an element which was regarded important but had less satisfactory performance; element which was already in accordance with users’ interest and expectation and thus could satisfy the users; element which was regarded less important and had less satisfactory performance; and elements of services which had good implementation but had less important influence on the users.Keywords: service quality, Students Satisfaction Index, Importance-Performance Analysis, library, research qualityAbstrak. Penelitian ini bertujuan untuk menganalisis kualitas pelayanan yang diberikan perpustakaan UPI kepada mahasiswa, mengetahui dan menganalisis sejauh mana tingkat kepuasan mahasiswa terhadap pelayanan perpustakaan UPI, dan mengetahui kesesuaian antara kinerja pelayanan dengan harapan atau kepentingan mahasiswa pengguna jasa layanan perpustakaan UPI dengan menggunakan analisis kepentingan dan kinerja (importance-performance analysis). Penelitian ini menggunakan desain gabungan antara kualitatif dengan kuantitatif untuk mengetahui indeks kepuasan mahasiswa dari layanan perpustakaan UPI. Teknik analisis datanya dilakukan dengan menggunakan nilai Indeks Kepuasan Masyarakat (IKM) yang dihitung dengan menggunakan nilai rata-rata tertimbang masing-masing unsur pelayanan. Importance-Performance Analysis dugunakan untuk melihat tingkat kesesuaian antara harapan dan kualitas pelayanan. Hasil penelitian menunjukkan bahwa kinerja pelayanan perpustakaan UPI termasuk dalam kategori baik. Unsur pelayanan yang dirasakan paling baik adalah berkaitan dengan keamanan pelayanan sedangkan pelayanan yang dinilai rendah adalah kedisiplinan petugas pelayanan. Selaian itu, ditemukan juga unsur pelayanan yang dinilai oleh responden sangat penting tetapi kinerjanya masih kurang memuaskan, unsur pelayanan yang dinilai oleh responden kinerjanya telah sesuai dengan kepentingan dan harapan pelanggan, sehingga dapat memuaskan pelanggan, unsur pelayanan yang menurut responden dianggap kurang penting pengaruhnya bagi pengguna jasa dan kinerjanya juga kurang bagus, dan unsur-unsur pelayanan yang menurut responden pelaksanaannya sangat baik tetapi kurang penting pengaruhnya bagi pelanggan.Kata kunci: Kualitas pelayanan, Indeks Kepuasan Mahasiswa, Importance-Performance Analysis, Perpustakaan, Mutu penelitian